The Relevance Of Citizen Lawsuit As A Positive Legal Instrument In The Procedural Law Of The State Administrative Court - Rosita Indrayati; Zensa Reginsa Putri; Diksi Natasia Salsabila (Jurnal Justiciabelen, 2023)
Citizen Lawsuit is a law enforcement process with a mechanism for filing a lawsuit by citizens. The implementation of Citizen Lawsuit in Indonesia is termed still gray because there are no specific laws or regulations that regulate the mechanism either substantively or procedurally. The basis of the existence of a Citizen Lawsuit is negligence or violation by the state administrator of the laws and regulations and the General Principles of Good Governance (AUPB). The Citizen Lawsuit mechanism deserves a deeper study, because in its development there have been many Citizen Lawsuit lawsuits submitted to the General Court in terms of environmental law enforcement, fulfillment of human rights, violations of the principles of good general governance, and so on. By looking at the essence of the Citizen Lawsuit, the idea emerged that the Citizen Lawsuit must be legally adopted as part of positive law in HAPTUN for the sake of legal enforcement and certainty. The study, entitled the relevance of Citizen Lawsuit as a positive legal instrument in the procedural law of the state administrative court, aims to examine and analyze how the concept of the Citizen Lawsuit mechanism in the perspective of the State Administrative Court and whether it can be adopted as part of its positive law. The author uses research methods with a normative juridical approach or legal research as well as scientific literacy literature studies. The author's ideas are expected to provide a more comprehensive view of the perspective of Citizen Lawsuit in State Administrative Procedural Law and the relevance of Citizen Lawsuit to positive law. Citizen Lawsuit in the perspective of HAPTUN relates to the subject matter of the Defendant, the claims in the lawsuit related to the demands of attitudes or actions by state administrators, and their functions or objectives in fulfilling the rights of citizens. The main reason for Citizen Lawsuit can be adopted into positive law is because the concept of Citizen Lawsuit never conflicts with laws and regulations, and in its implementation provides many solutions to existing citizen problems and improves the implementation of the rights of citizens by state administrators. However, it is necessary to review the mechanism of Citizen Lawsuit in making positive law by adapting and adjusting to the Indonesian legal system so that in practice it can run effectively and optimally.